Evaluation Model for Teaching Quality of Physical Education: 體育教學品質評估模式 - HUNG, Chang Hung; SU, Jung Chi; CHEN, Wen Tzung (Asian Journal of Physical Education & Recreation, 2009)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. This study seeks to build an evaluation model for physical education. Based on the concept of physical education quality, the questionnaire for physical education is constructed. Binominal probability distribution theory is applied to evaluate the proportion of the degree of importance and satisfaction for physical education. To evaluate the quality of physical education, the PZB concept proposed by Parasurman, Zeithaml and Berry (1985) is used to test the difference between the proportion of the degree of importance and satisfaction. Each quality performance item of education could be evaluated by figuring out the difference between the proportion of the degree of importance and satisfaction, therefore the improvement or correction could be taken if needed. 本研究旨在建構一套體育教學品質評量模式，首先以體育教學品質概念作為體育教學品質問卷建構的基礎，並以二項分配理論衡量體育教學要項的重視度比例與滿意度比例，接著以PZB服務品質落差的概念，檢驗滿意度比例與重視度比例的落差，來評估體育教學品質的良窳。教學單位只須依教學品質要項的滿意度比例及重視度比例的落差，即可評量出各教學要項的品質績效，並針對須要改進的要項進行改善。